Exploring creativity and wellbeing characteristics of portuguese tourists - Garcês, Soraia (2021)
The purpose of this study was to explore creativity and wellbeing characteristics in a sample of Portuguese tourists while simultaneously building a creative tourist profile. A sample of 857 Portuguese tourists with ages ranging from 17 to 76 years was used. The Creative Personality Scale short form and the Tourism Experience Scale were applied for data collection. The results indicated positive and significant correlations between wellbeing and creativity. Women showed higher levels of wellbeing. Older tourists performed better in creativity. Age had a significant influence only on creativity and not on tourists’ overall wellbeing. Non-students obtained higher and significant scores for creativity, while overall wellbeing was not influenced by having a job (student vs non-student). A significant multiple linear regression model suggested that wellbeing and age are significant predictors of creativity in tourism settings. Wellbeing rankings showed positive emotions in first place, creativity in second place and meaning in third place. In conclusion, the results indicated that creativity and wellbeing are important factors for tourism experiences and that Portuguese tourists’ psychological profile already show